Хроматографічне визначення летких сполук Achillea micranthoides Klok. et Krytzka - Дуюн, Ірина Федорівна; Панченко, Світлана Валеріївна; Duiun, I. F.; Panchenko, S. V. (Запорізький державний медико-фармацевтичний університет, 2024)
Мета роботи – вивчити леткі сполуки екстракту деревію подового трави (Achillea micrantoides Klok. et Krytzka) і встановити їхній компонентний склад. Матеріали і методи. За допомогою методу тонкошарової хроматографії та метoду газової хромато-мас-спектрометрії на хроматографі Agilent Technology 7890 B визначили компонентний склад летких сполук Achillea micranthoides Klok. et Krytzka. Для ідентифікації компонентів проб використали бібліотеку мас-спектрів NIST14. Результати. Ідентифікацію компонентів летких сполук здійснили методом тонкошарової хроматографії за допомогою етилацетатних витягів із листя та суцвіть виду, що досліджували. Як рухому фазу використали етилацетат-толуол у співвідношенні (5:95). Методом газової хромато-мас-спектрометрії визначено наявність 30 летких сполук у траві A. micranthoides Klok. et Krytzka, серед них ідентифіковано 26 сполук, що становило 86,76 % від загальної кількості. Aim. The purpose of the work is to study the volatile compounds of the yarrow extract (Achillea micrantoides Klok. et Krytzka) and to establish their component composition. Materials and methods. The Thin-Layer Chromatography (TLC) method and Gas Chromatography-Mass Spectrometry (GC/MS) on an Agilent Technology 7890 B chromatograph were employed to determine the component composition of volatile compounds in Achillea micranthoides Klok. et Krytzka. The NIST14 mass spectral library was utilized for identifying the components of the samples. Results. Identification of volatile compound components was carried out by chromatography of ethyl acetate extracts from the leaves and inflorescences of the subject TLC in the mobile phase ethyl acetate – toluene (5:95). By the gas method Chromatography-mass spectrometry determined the presence of 30 volatile compounds of grass A. micranthoides Klok. et Krytzka, 26 of the compounds were identified, which accounted for 86.76 % of the total number of compounds.
Chromatographic determination of volatile compounds of Achillea micranthoides Klok. et Krytzka
Дуюн І. Ф. - ORCID ID: 0000-0003-1134-2543; Панченко С. В. - ORCID ID: 0000-0002-6668-1959.
Keywords: Achillea micranthoides Klok. et Krytzka; газова хромато-мас-спектрометрія; леткі сполуки; етанольні екстракти; gas chromato-mass-spectrometry; volatile compounds; ethanol extracts